Therapeutic potential inhibitor for dipeptidyl peptidase IV in diabetic type 2: In silico approaches - Roney, Miah; Dubey, Amit; Nazim Uddin, Mohammed Nazim; Issahaku, Abdul Rashid; Tufail, Aisha; Tufail, Nasir; Wilhelm, Anke; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer Science and Business Media Deutschland GmbH, 2025)
Diabetes mellitus (DM) is a metabolic disease marked by an excessive rise in blood sugar (glucose) levels caused by a partial or total absence of insulin production, combined with alterations in the metabolism of proteins, lipids, and carbohydrates. The International Diabetes Federation estimates that 425 million individuals globally had diabetes in 2017 which will be 629 million by 2045. Several medications are used to treat DM, but they have limitations and side effects including weight gain, nausea, vomiting, and damage to blood vessels and kidneys. Therefore, it is essential to identify anti-diabetic drugs that have less or no side effects. Hence, the current study employed in silico approaches to discover new DPP-IV inhibitors that might be associated with diabetes. Thirty-four (34) co-crystalized DPP-IV enzymes were found from the protein data bank and the co-crystal ligands were docked into the active-site 6B1E protein to find out the hit compounds. From the docking results, we found two hit compounds (5T4E and 4J3J) which were used to find out the analogs from the experimental drug database using the DrugRep software. According to the results, twenty (20) analogs were found from the experimental drug database with the similarity score of ≥ 0.790 and docked once again into the active site of the DPP-IV (PDB ID: 6B1E) enzyme. Interestingly, DB02226 showed the best binding affinity (−10.3 kcal/mol) and prime MM/GBSA (−68.73 kcal/mol) compared to the reference drug (co-crystal ligand; −7.4 kcal/mol and −47.49 kcal/mol, respectively). Additionally, DB02226 has shown excellent reactivity, efficacy, and structural stability in the binding region of target proteins in studies using MD simulation, MM/GBSA, DFT, and MESP analysis. These findings can be utilized to support further in vitro, in vivo, pre-clinical and clinical research rather than definitively confirming anti-diabetic effectiveness.